Almost the same stories: narrative patterns in EU treaty referendums - Schünemann, Wolf J. (National identities, 2017)
The article analyses narratives that favoured or opposed European integration in three referendum debates held during the constitutional process of the 2000s: in France and the Netherlands in 2005 (Constitutional Treaty) as well as the first vote in Ireland on the Lisbon Treaty in 2008. In all debates examined, speakers used similar narratives of European integration. While most narrative patterns have transnational character, however, they are also remarkably country-specific. They depend on the specific cultural context and the social positions of the speakers articulating them.